The implementation of affective and psychomotor assessment in Islamic religious education learning in Junior High Schools - Wijaya, Asep; Andriani, Reki Tri; Ismady, Muhammad Wali; Septria Darma Suwarni, Wenty; Ahzim, Rezani (TARBAWY: Indonesian Journal of Islamic Education, 2023)
Psychomotor and affective assessments are still rarely carried out so that the assessment results are not optimal. This research aims to analyze the implementation of affective and psychometric assessments in Islamic Religious Education learning. This research uses a qualitative approach. The data collected was analyzed using the interactive model from Miles Huberman. The results of the assessment discussion are a benchmark used in determining student learning outcomes. The assessment at this research location, namely at SMPN 03 Rejang Lebong, is determined by the school but still takes into account the KKM that has been determined. Teachers gain an understanding of assessment through seminars or training workshops. The affective assessments used by PAI teachers at SMPN 3 Rejang Lebong include observation, self-assessment, journals and peers. Meanwhile, the psychomotor assessment uses performance techniques and tests in the form of simulations and checklists.Penilaian psikomotorik dan afektif masih sangat jarang dilakukan sehingga hasil penilaian kurang maksimal. Penelitian ini bertujuan untuk menganalisis pelaksanaan penilaian afektif dan psikomotrik pada pembelajaran Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kualitatif. Data yang dikumpulkan dianalisis dengan interactive model dari Miles Huberman. Hasil pembahasan penilaian adalah sebuah tolak ukur yang digunakan dalam menentukan hasil belajar siswa. Penilaian di lokasi penelitian ini yaitu di SMPN 03 Rejang Lebong, ditentukan oleh pihak sekolah namun tetap mempertimbangakan KKM yang telah ditetapkan. Guru memperoleh pamahaman penilaian melalui seminar atau worksop pelatihan. Penilaian afektif yang digunakan guru PAI di SMPN 3 Rejang Lebong di antaranya adalah observasi, penilaian diri, jurnal, dan teman sejawat. Sedangkan pada penilaian psikomotorik menggunakan teknik unjuk dan tes berupa simulasi dan daftar cek.